G263(P) The treatment of anorexia nervosa in adolescents: a metasynthesis of parents' perspectives. (25th October 2020) - Oketah, ON; Frost, P
Abstract : Background: Anorexia nervosa (AN) is a severe eating disorder with onset typically in adolescence characterised by a distorted body image major and an intense fear of weight gain. It greatly impacts on adolescent growth, puberty and psychological development and is known to have the highest mortality of any psychiatric illness. Treatment is challenging and studies have established the central role of the family in recognition, treatment and recovery from anorexia. Objectives: The aim of this research was to perform a systematic review of all qualitative studies done on the views of parents on the treatment and recovery process of anorexia nervosa in their adolescent child. Methods: A systematic search of six databases: Medline, PsychINFO, CINHAL, EMBASE, Cochrane library and SSCI was conducted for qualitative studies regarding parents' views about the treatment of anorexia nervosa in adolescents. Quality of articles was assessed using the critical appraisal skills program (CASP). The chosen studies were analysed and key themes identified using thematic synthesis. Results: In total, the systematic search yielded 315 papers of which 14 studies from six countries met my inclusion criteria reporting the views of 202 parents. Four themes were developed from the analysis: Understanding the child and the disease, Experience of services and treatment modalities, the role of professionals and the concept of recovery. Conclusion: This is the first systematic review performed so far focussing solely on parents views on adolescent AN treatment and further highlights the importance of taking into account parents views in the treatment of adolescent anorexia. While they report relief in finding help at a very difficult time in their life, they continue to struggle with delays in finding help, judgmental attitudes of professionals and uncertainty about the future. Recognition by clinicians of the challenges faced by parents and families will help to provide better support, and a more holistic approach and hopefully reduce the burden of chronicity of adolescent anorexia into adulthood.